Mortal gods - Blake, Kendare (Blake, Kendare. Goddess war, 2014)
The escalating war between the gods takes Athena and Cassandra across the globe, searching for lost gods, old enemies, and the great warrior, Achilles, and although their alliance is fragile, they must find a way to work together or all is lost.